KEPASTIAN HUKUM KEPEMILIKAN SERTIFIKAT HAK ATAS TANAH TUMPANG TINDIH PERSPEKTIF PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (STUDI KASUS: PUTUSAN PENGADILAN NEGERI TANJUNG PINANG NOMOR: 52/PDT.G/2020/PN.TPG) - Aditya Luthfi Denia; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2022)
Soil as an essential source of life for humans, fauna, and flora must be maintained. ownership of a plotof land by a person is marked by the ownership of a land certificate. A land title certificate is proof ofa person's ownership of a land and its buildings. The author uses normative legal research methodsand uses interview data as supporting data. The results of the study reveal that a certificate indicatingownership of a piece of land is regulated in Government Regulation Number 24 of 1997 concerningLand Registration. Court Decision Number 52/PDT.G/2020/PN.TPG is used by researchers to assesslegal certainty and legal remedies that can be taken in the event of an overlapping dispute over landcertificates claimed by several parties. The results of this study are land certificates are very strongevidence for proof in court where the certificate that is recognized as true is a certificate issued first bythe land of ice and if there are overlapping land certificates, the actual owner can file a lawsuit to thedistrict court or court state administration to cancel other certificates.